Characterizations of motivation and identity in medical students' reflections about challenging patient interactions. (3rd October 2019) - Steinauer, Jody E.; Teherani, Arianne; Mangini, Robin; Chien, Jessie; ten Cate, Olle; O'Sullivan, Patricia
Abstract: Purpose: Students' negative emotions in patient interactions can relate to their learning motivation and identity. Educators can support learning from these interactions by advocating for reflection. We explored how students, in reflection essays about emotionally difficult patient interactions that challenged their notions of professionalism, described aspects of motivation and identity. Materials and Methods: All third-year medical students on the ob-gyn clerkship complete written reflections about a "clinical situation that challenged or affirmed your professionalism." We conducted directed content analysis of essays (academic years 2014–2017) using relevant theories (self-determination, goal orientation and identity formation) based on previous work and organized the data into categories. Results: In 265 essays (of 396, 67%), students described patient interactions that challenged their notions of professionalism, of which 90% included descriptions of their emotions. When reflecting on these interactions, students described psychological needs acknowledged in self-determination theory, competence, autonomy in patient care and connection to the team. Students indicated challenges in identity when advocating for patients due to team hierarchy and evaluation concerns. Conclusions: Reflection essays about difficult patient interactions allow students to explore emotions, motivation and identity. They help educators understand whether the clinical learning environment is meeting students' needs to support learning in challenging interactions.